Healthy life expectancy of oral squamous cell carcinoma patients aged 75 years and older. (January 2017) - Yamada, Shin-ichi; Kurita, Hiroshi; Tomioka, Takahiro; Ohta, Ryousuke; Yoshimura, Nobuhiko; Nishimaki, Fumihiro; Koyama, Yoshihito; Kondo, Eiji; Kamata, Takahiro
Highlights: The aim of study was to analyze self-reliance survival (SS) times of OSCC patients. Median SS times of aged 75–79, 80–84, and over 85 years were 5.7, 1.6, and 1.4 years. SS time may be one of the measures of patient prognosis as well as OS times. Abstract: Objectives: Healthy life expectancy, an extension of the concept of life expectancy, is a summary measure of population health that takes into account the mortality and morbidity of a population. The aim of the present study was to retrospectively analyze the self-reliance survival times of oral squamous cell carcinoma (OSCC) patients. Materials and methods: One hundred and twelve patients aged 75 years or older with primary OSCC were included and examined at Shinshu University Hospital. To investigate healthy life expectancy, OSCC patients older than 75 years were divided into 3 groups: 75–79, 80–84, and older than 85 years. The Kaplan-Meier method was used to estimate the median times of healthy life expectancy. The Log-rank test was used to test significant differences between actual curves. Results: The median self-reliance survival times of patients aged 75–79, 80–84, and older than 85 years were 5.7, 1.6, and 1.4 years, respectively. Most patients with early stage cancers underwent curative treatments and showed a health expectancy of more than 5 years. In patients with advanced cancers, health expectancy was poor (less than one year), except among patients aged 75–79 years who underwent standard treatments. Conclusions: It seems that in patients with advanced cancers, health expectancy was poor (less than 1 year), except among patients aged 75–79 years who underwent standard treatments. In elderly patients, healthy life expectancy (self-reliance survival time) may be one of the measures of patient prognosis as well as overall survival times.